Faktor-faktor yang berhubungan dengan pemanfaatan pelayanan posyandu lansia - Rahman Makaminan; Greta Jane Pauline Wahongan; Martha Marie Kaseke (Holistik Jurnal Kesehatan, 2026)
Background: The elderly population undergoes an aging process that renders them vulnerable to various physical, mental, and social health issues. As the number of elderly individuals in Indonesia rises, the need for affordable and sustainable healthcare services becomes increasingly critical. One government initiative aimed at improving the health status of the elderly is the implementation of integrated service posts for the elderly. However, the utilization rate of these services remains suboptimal in many areas, including the working area of ​​the Gemeh Community Health Center in Talaud Regency. Purpose: To analyze the relationship between family support, the role of health workers, and attitudes toward the utilization of integrated service posts for the elderly. Method: This study employed a quantitative, cross-sectional design and was conducted in the working area of ​​the Gemeh Community Health Center, Talaud Regency, between February and April 2026. The study population consisted of 600 elderly individuals aged 60–70 years. A sample of 200 respondents was determined using Slovin's formula and selected via simple random sampling. Data collection was carried out using a questionnaire that had undergone validity and reliability testing. Data analysis included univariate analysis, bivariate analysis using the Chi-Square test, and multivariate analysis using multiple logistic regression. Results: This study reveals that 63.3% of respondents utilized the integrated service post for the elderly. The majority of respondents received family support (92%), rated the role of health workers as "good" (58.5%), and held an attitude categorized as "low" regarding the utilization of the integrated service post for the elderly (54.5%). Bivariate analysis showed a significant association between family support (p = 0.038), the role of health workers (p = 0.030), and attitude (p = 0.010) with the utilization of the integrated service post for the elderly. Furthermore, multivariate analysis revealed that attitude was the most dominant factor associated with the utilization of the integrated service post for the elderly (p = 0.010; OR = 0.453; 95% CI = 0.249–0.826) compared to the other variables. Conclusion: Family support, the role of healthcare workers, and attitudes are significantly associated with the utilization of integrated service posts for the elderly. However, attitude is the most dominant factor related to the use of these services. Suggestion: Efforts are needed to enhance health education, strengthen the role of families, and optimize the role of healthcare workers in providing counseling and support to the elderly in order to increase the utilization of integrated service posts for the elderly.   Keywords: Attitude; Elderly; Family Support; Health Service Utilization; Integrated Health Post; Role of Health Workers.